Sport and the Media in Brazil: Vices and Virtues of a Secular Marriage - Marques, José Carlos [UNESP] (Springer Nature, 2021)
This article aims to analyze the particularities of the coverage conducted by printed media, radio, and television in Brazil regarding the sports scene, in a historical retrospective dating back to the first half of the twentieth century and extending to the second decade of the twenty-first century. We start from the assumption that, nowadays, sport represents a phenomenon with several consequences, since different sporting modalities—and, in the case of Brazil, football in particular—launch fashions and behaviors, stimulate the advertising world and the global economy, promote the emergence of technological innovations and create identity relations among different social groups. Thus, the text seeks to find correlations between the way of approaching sports in newspapers, radio stations and TV stations, in a period and a scenario that precedes the entry of the Internet as a potentiator of the presence of sport in different media.
Keywords: Brazilian press; Football; Media; Sport